Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ajt.17092
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of ABMR with or without donor-specific antibody in kidney transplant biopsies: Differences in timing and intensity but similar mechanisms and outcomes

Abstract: We studied the clinical, histologic, and molecular features distinguishing DSA‐negative from DSA‐positive molecularly defined antibody‐mediated rejection (mABMR). We analyzed mABMR biopsies with available DSA assessments from the INTERCOMEX study: 148 DSA‐negative versus 248 DSA‐positive, compared with 864 no rejection (excluding TCMR and Mixed). DSA‐positivity varied with mABMR stage: early‐stage (EABMR) 56%; fully developed (FABMR) 70%; and late‐stage (LABMR) 58%. DSA‐negative patients with mABMR were usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…[27][28][29] Archetypal analysis automatically assigns scores to each biopsy describing its relationship to each archetype group: no rejection, TCMR1 (active TCMR, often mixed), TCMR2 (less active TCMR), early stage AMR, fully developed AMR, and late-stage AMR, which is often relatively inactive. 20,29 Archetypes recognize only the dominant phenotype and do not designate a separate mixed category.…”
Section: The Molecular Microscope Diagnostic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Archetypal analysis automatically assigns scores to each biopsy describing its relationship to each archetype group: no rejection, TCMR1 (active TCMR, often mixed), TCMR2 (less active TCMR), early stage AMR, fully developed AMR, and late-stage AMR, which is often relatively inactive. 20,29 Archetypes recognize only the dominant phenotype and do not designate a separate mixed category.…”
Section: The Molecular Microscope Diagnostic Systemmentioning
confidence: 99%
“…15,16 Another test widely used to assess risk of rejection is the donor-specific HLA antibody (DSA) to predict antibody-mediated rejection (AMR), but this has been complicated by the recognition of DSA-negative AMR. 17-20…”
Section: Introductionmentioning
confidence: 99%
“…Although all active ABMR cases had anti-HLA DSA in this study, WARS1 and TYMP showed a diffuse microcirculation pattern in most C4d negative cases, highlighting their potential interest in this context. As non-anti-HLA DSA are still not routinely tested, the diagnosis of such ABMR cases with no detectable anti-HLA DSA ultimately relies on C4d in daily practice, which is not known to perform well in this setting 33 , 34 , with up to 86% of C4d-negative cases in a recent transcriptomic study 35 . By highlighting a diffuse endothelial staining by immunohistochemistry, WARS1 and TYMP could be of great interest in these cases and this needs to be assessed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that DSA negative microvascular inflammation has a similar prognosis to DSA positive microvascular inflammation 29,30 . In addition, recent studies suggest that molecular signatures do not distinguish between HLA DSA positive and HLA DSA negative cases 31,32 . Since all the patients in our cohort had previously had DSA and the activated molecular pathways (presumably targeted by tocilizumab) are the same between DSA positive and DSA negative cases, we included all 38 cases in our study.…”
Section: Discussionmentioning
confidence: 99%